Comparison of Cut-Off Value of Neutrophil to Lymphocyte Ratio in the Diagnosis of Non-Perforated Versus Perforated Appendix: Non-Perforated Versus Perforated Appendix - Abbas, Mudasir; Ghayour, Lyba; Deen, Qaim; Nadeem, Muhammad; Ahmed, Khawaja Salman; Siddique, Muhammad (Pakistan Journal of Health Sciences, 2025)
Neutrophil-To-Lymphocyte Ratio (NLR) gives diagnostic clue about non-perforated and perforated appendixes. However, there are many variations in its cut-off values in diagnosis of non-perforated and perforated appendixes, and there is no single value to differentiate severity of appendicitis. Objective: To determine the optimal NLR cutoff value for diagnosing perforated vs. non-perforated appendicitis in patients presenting with acute appendicitis. Methods: This cross-sectional analysis was carried out at Surgical Department of Mayo Hospital, Lahore from July 2022 to January 2023. Total 105 patients with acute appendicitis undergoing open appendectomy were enrolled after written informed consent. The patients were grouped according to perforated and non-perforated appendicitis, and NLR value was compared in both groups. Continuous and categorical variables were presented as mean ± SD and frequency (%). Results: Non-perforated appendix group comprised 84 (80%) patients, whereas perforated appendix group comprised 21 (20%) patients. Mean NLR in perforated appendicitis group was higher as compared to non-perforated group (14.7 ± 12.6 vs. 7.36 ± 8.93, p = 0.01). Cut-off point for NLR was obtained at 5.71, with sensitivity and specificity noted was 66.7 % and 62%, respectively. Conclusions: The study highlighted the potential of NLR as predictive marker for distinguishing between perforated and non-perforated appendicitis. Its clinical utility is supported by identified cut-off value of 5.71, suggesting its role in aiding timely intervention and reducing complications. The findings reinforce the importance of NLR, particularly in identifying patients at higher risk of appendiceal perforation.